2017
DOI: 10.7717/peerj.2886
|View full text |Cite
|
Sign up to set email alerts
|

Jaguar interactions with pumas and prey at the northern edge of jaguars’ range

Abstract: We present the first study that evaluates jaguar-puma interactions in the arid lands of northern Mexico, where jaguars have their northernmost breeding population and both predators are persecuted for livestock depredation. We tested whether jaguars are the dominant species in this unique ecosystem, where: (1) pumas outnumber jaguars, (2) pumas are better adapted to arid environments, and (3) jaguars and pumas are of similar size. We analyzed four years of data with two approaches; a two species conditional oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
(93 reference statements)
2
23
0
2
Order By: Relevance
“…Overall, the general pattern was suggestive that the size difference between pumas and other apex predators does correlate with dominance. For example, evidence that jaguars are dominant is strongest in areas where jaguars are large and weigh considerably more than pumas, but more ambiguous where the two species are more similar in size ( López-González & González-Romero, 1998 ; Gutiérrez-González & López-González, 2017 ). Wolf packs also appear to have a clear advantage over individual pumas, but one-on-one, the outcome of competitive interactions between a wolf and a puma is less certain ( Ruth & Murphy, 2010 ) or dependent upon differences in age (e.g., wolves killing puma kittens; Elbroch et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the general pattern was suggestive that the size difference between pumas and other apex predators does correlate with dominance. For example, evidence that jaguars are dominant is strongest in areas where jaguars are large and weigh considerably more than pumas, but more ambiguous where the two species are more similar in size ( López-González & González-Romero, 1998 ; Gutiérrez-González & López-González, 2017 ). Wolf packs also appear to have a clear advantage over individual pumas, but one-on-one, the outcome of competitive interactions between a wolf and a puma is less certain ( Ruth & Murphy, 2010 ) or dependent upon differences in age (e.g., wolves killing puma kittens; Elbroch et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Such studies offer insights into competitive interactions and mechanisms of coexistence, however, this difference in methods likely accounts for the large number of publications in which researchers report that they did not detect any competition between jaguars and pumas ( Table 2 ). Whereas some authors were certain they found evidence that jaguars were dominant over pumas (e.g., Harmsen et al, 2009 ), other researchers, from areas where jaguars are smaller and sometimes numerically fewer than pumas, suggested the two species may be at least equal in competitive interactions, or even that pumas may be dominant over jaguars (e.g., Gutiérrez-González & López-González, 2017 ). We did discover five references that report incidents of jaguars killing pumas (e.g., Crawsha Jr & Quigley, 1984 ; Harmsen et al, 2009 ), whereas we did not find a single documentation of the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both variables, NDVI and capture rate of prey, could reflect the potential availability of prey, but at different temporal and spatial scales. It is worth noting that prey abundance ranked as the most important variable impacting the habitat use of jaguars here and other regions (Gutiérrez-González & López-González, 2017; Santos et al., 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Because of the greater morphological similarity between jaguar and puma, we expected a lower degree of overlap between them compared to jaguar-ocelot and puma-ocelot pairs, but this was not confirmed. However, other studies observed that top predators exhibit similar daily activity cycles [44,80,81], indicating that some degree of temporal overlap would be expected from the similar dietary profiles of jaguars and pumas. It is more likely that the general temporal patterns can be related to the attractiveness of food resources, rather than avoidance of a larger predator [11,67].…”
Section: Discussionmentioning
confidence: 99%